THE ROLE OF RELIGIOUS EDUCATION TO REDUCE RADICALISM OF ELEMENTARY TEACHER EDUCATION STUDENTS - Santosa, Donald Samuel Slamet (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study started from the problem of radicalism found among students of Elementary Teacher Education (ETE). The purpose of this study was to analyze the role of religious education courses in reducing radicalism among ETE students. This study is action research using the Kemmis Tagart model. The study was conducted in one class with 37 students who have different religion. Religious education courses were designed in such a way, starting from the syllabus, learning content, learning process, to media and teaching aids, so that it was ensured to be able to reduce student radicalism. Pretest and posttest data were collected using test techniques to measure the level of student radicalism. The collected data were analyzed using the mean difference test technique with the help of SPSS. The results of the study showed that this course was successful in reducing radicalism among ETE students.